Cauda Equina Syndrome Without Perineal Sensory Changes or Lower Extremity Neurological Deficits Following Postoperative Spinal Epidural Hematoma: A Case Report and Literature Review - Guanyi Liu; Qing Li; Hongfeng Ruan; Bingke Zhu; Weihu Ma; Yong Hu (Orthopaedic Surgery)
ABSTRACT Background Postoperative spinal epidural hematoma (SEH) is a rare but serious complication following lumbar surgery, with cauda equina syndrome (CES) being one of its most devastating outcomes. While CES typically presents with a combination of bladder and/or bowel dysfunction, diminished sensation in the saddle area, and motor or sensory changes in the lower limbs, atypical cases with isolated urinary symptoms are less recognized and pose significant diagnostic challenges. Case Presentation We report the case of a 46‐year‐old male who developed CES following lumbar microdiscectomy, presenting solely with urinary retention, without the classic signs of lower limb weakness or perineal sensory loss. Initial symptoms were attributed to postoperative urinary issues, delaying the diagnosis of CES. On postoperative day 7, magnetic resonance imaging (MRI) revealed SEH, and emergency hematoma evacuation was performed. Despite the delayed intervention, the patient made a full neurological recovery, with bladder and bowel functions restored by 3 months postoperatively. Conclusion This case highlights the importance of recognizing CES in patients with isolated urinary dysfunction after lumbar surgery, even when typical neurological symptoms such as lower limb weakness or perineal sensory loss are absent. Early detection and prompt surgical intervention are critical, as delayed diagnosis may result in permanent neurological deficits. Moreover, this case underscores the need for vigilant postoperative monitoring, especially of urinary function, as isolated urinary symptoms may signal early CES. Maintaining a high index of suspicion for CES, even in atypical presentations, can facilitate timely diagnosis and improve patient outcomes. Furthermore, this case highlights the need for continued research into the prevention of SEH and the development of more robust diagnostic criteria for CES in postoperative patients. Future studies should focus on developing more comprehensive guidelines for monitoring postoperative patients, especially regarding urinary function, to aid in the early detection of CES.